Calcifying odontogenic cyst: A case report (Research, Society and Development, 2024)
The Calcifying Odontogenic Cyst (COC), also known as Gorlin's cyst, is a rare entity with histological variability, giving rise to terminological discussions. Despite attempts at standardization, discrepancies persist due to its biological complexity. Accounting for only 0.3% of oral biopsies, COC originates from remnants of the odontogenic epithelium, preferably in the maxilla. Its incidence shows no gender bias, occurring more frequently in the 20s and 30s, with a slow and asymptomatic evolution. The lesion can be associated with other odontogenic pathologies. Radiographically, it appears radiolucent, either unilocular or multilocular, with well-defined or poorly defined margins. Histological examination reveals a fibrous cystic wall with odontogenic epithelium, highlighting ghost cells. The recommended treatment is enucleation combined with curettage, with a low risk of recurrence, requiring evaluation in cases associated with other lesions. The restoration of compromised bone structures demands contemporary approaches to bone grafting and special periodontal interventions. The study presents a detailed case report of a COC in the anterior right maxilla, employing a descriptive and qualitative approach. The clinical case involves a 57-year-old patient with COC in the anterior right maxilla, treated with enucleation, curettage, and xenogeneic bone grafting. Histological analysis confirmed the diagnosis. A 1.5-year follow-up reveals favorable evolution, with bone neoformation and no signs of recurrence. This case report aims to add knowledge about this rare lesion and its clinical and radiographic aspects, as well as its diagnosis, possible prognosis and treatment.